2020
DOI: 10.1038/s43247-020-00042-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved forecasts of atmospheric rivers through systematic reconnaissance, better modelling, and insights on conversion of rain to flooding

Abstract: Atmospheric rivers lie behind many extreme precipitation and flood episodes in the mid-latitudes. Better forecasts of atmospheric rivers and their impacts could help with preparedness. Here we argue that a comprehensive and systematic observational campaign could help advance numerical weather prediction, and thereby provide a path towards much improved forecasts of atmospheric rivers. We envision an interdisciplinary European–American observational campaign in the North Atlantic to identify and address numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…We therefore propose an alternative way to model the wet tropospheric delays, through a representation of the wet refractivity field as a perturbation over an exponential decay with altitude with a locally adjusted scale height and a time/space series expansion over a suitable basis of orthogonal functions. Our approach is computationally expensive, and maybe not suited for real-time applications, but its end-product are records of the total and wet refractivity values with high-resolution in time (minute-scale) and distance (sub km-scale), in accordance with the needs of future numerical weather models [38], the emerging field of the modeling of atmospheric rivers [100,101] and besides does not require the additional step of water vapor tomography, with lower cost, better mobility and simpler operation [102].…”
Section: Resultsmentioning
confidence: 99%
“…We therefore propose an alternative way to model the wet tropospheric delays, through a representation of the wet refractivity field as a perturbation over an exponential decay with altitude with a locally adjusted scale height and a time/space series expansion over a suitable basis of orthogonal functions. Our approach is computationally expensive, and maybe not suited for real-time applications, but its end-product are records of the total and wet refractivity values with high-resolution in time (minute-scale) and distance (sub km-scale), in accordance with the needs of future numerical weather models [38], the emerging field of the modeling of atmospheric rivers [100,101] and besides does not require the additional step of water vapor tomography, with lower cost, better mobility and simpler operation [102].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that EP events are increasing worldwide due to global warming, which is likely to continue in the coming decades (AghaKouchak et al., 2020; Li et al., 2020, 2021; Scoccimarro et al., 2013). Atmospheric rivers (ARs, Zhu & Newell, 1994), moisture passages that carry large amounts of water vapor in the mid‐latitudes, have been identified as a critical driver of EP events (Gimeno et al., 2014; Kamae et al., 2021; Lavers et al., 2014, 2020; Payne et al., 2020; Ralph et al., 2006; Waliser & Guan, 2017). Studies have demonstrated that the occurrence of ARs can be used as a reliable predictor of EP as it has a high predictability (Chen et al., 2018; Lavers & Villarini, 2013, Lavers et al., 2014; Lavers & Villarini, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric rivers (AR) are widely recognized as being important for water resources and impacts in western coastal zones, with nearly 30 years of research establishing their meteorological context (Neiman et al, 2002;Ralph et al, 2018;Rutz et al, 2019;Shields et al, 2018, and references therein), AR variability and change (Cao et al, 2020;Dettinger, 2011;Dong et al, 2018;Espinoza et al, 2018;Gao et al, 2015;Gershunov et al, 2017;Hagos et al, 2016;Lora et al, 2017;Ma & Chen, 2022;McClenny et al, 2020;Mundhenk et al, 2016Mundhenk et al, , 2018O'Brien et al, 2021;Payne & Magnusdottir, 2015;Payne et al, 2020;Reid et al, 2021;Rhoades et al, 2020;Warner & Mass, 2017;Warner et al, 2015;Zhou et al, , 2021, and AR forecasting (Cao et al, 2021;DeFlorio et al, 2018DeFlorio et al, , 2019Lavers, Pappenberger, et al, 2016;Lavers, Waliser, et al, 2016;Lavers et al, 2020;Zheng et al, 2021). The list of topics and citations here is meant to be illustrative rather than exhaustive; there are now hundreds of AR papers in the literature.…”
Section: Introductionmentioning
confidence: 99%